SIFAT KIMIA TANAH DAN POPULASI KUMBANG TANDUK (Oryctes rhinoceros L.) STADIA PRADEWASA PADA BERBAGAI KEDALAMAN PENEMPATAN TANDAN KOSONG KELAPA SAWIT - Hafiz Fauzana; Ayubi Alfasiri; Nelvia Nelvia (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2019)
Oil palm is a very significant industrial plant in producing vegetable oils that require high levels of nutrients in its cultivation. Cultivation of oil palm yield can produce industrial waste, the oil palm empty trunks (TKKS) which have the potential to supply nutrients to oil palm land. The placement of empty trunks at various depths is expected can give effect to the population of Oryctes rhinoceros L pre-adult stage and chemical soil properties. This research was conducted on oil palm plantation in PT. Perkebunan Nusantara V Sei Galuh Tapung, Kampar, Riau from July to October 2017. The aim of this research is to examine the effect of empty trunks placement against the Oryctes rhinoceros L population development and chemical soil properties. This research was done using a randomized experiment design complete with the treatment of the depth empty trunks placement (placement of oil palm empty trunks on the ground at the depth of 10 cm, 20 cm, and 30 cm) which is repeated four times. The observed parameters include the population of infestation of Oryctes rhinoceros L (population of eggs, larvae and pupae) and soil chemical properties (soil pH, C-organic, N-total, P-total and K-total). The results showed that empty trunks placed below the surface at various depths affected the Oryctes rhinoceros L population. Placement of TKKS depth in the soil cannot be infested by Oryctes rhinoceros L. Placement of empty trunks at the depth of the soil tends to increase pH (from very acidic categories to acidic categories) and total K (from the low category to very high category), is not effected on C-organic and N-total and can reduce P-total (from the very high category to the high category) if compared to the placement of empty trunks on the ground.Key words : Chemical Soil properties, Oryctes rhinoceros L., Oil palm Empty trunks, Soil depth